EFFECT OF MONOSODIUM GLUTAMATE ON THE SERUM ESTROGEN AND PROGESTERONE LEVELS IN FEMALE RAT AND PREVENTION OF THIS EFFECT WITH DILTIAZEM - Zia, Muhammad Sarwar; Qamar, Khadija; Hanif, Ruhila; Khalil, Moazzam (Journal of Ayub Medical College Abbottabad, 2014)
Background: Glutamate is found in a wide variety of foods. It induces the uterine fibroid in the rats by increasing the levels of estradiol. Diltiazem is an effective preventive medication. This study was conducted to analyse the effect of monosodium glutamate on the serum estrogen and progesterone levels in adult Sprague Dawley rat and its prevention with diltiazem. Methods: This Laboratory based randomized controlled trial was conducted in the department of Anatomy, Army Medical College, Rawalpindi in collaboration with National Institute of Health (NIH), Islamabad from 9th April to 23rd April 2012. In this experimental study, 30 adult female Sprague Dawley rats of average weight of 500 g were randomly assigned into three groups. The experimental group B was given 0.08 mg/kg of monosodium glutamate (MSG) orally and experimental group C was given 0.08 mg/kg of MSG and 10 mg/kg of diltiazem in distilled water orally for 14 days. The control group (A) received only laboratory diet. Using intracardiac route 5 ml blood was taken from each animal for hormonal assay. Results: Hormone assay of the serum in the experimental group B showed increase in serum estrogen and progesterone levels as compared to the group A and there was minor increase in the hormonal levels in group C. Conclusion: MSG causes increase in the serum estrogen and progesterone levels in adult female rats and diltiazem prevents this effect. Keywords: Diltiazem, Estrogen, Monosodium Glutamate, Progesterone